Information Systems, Logistics, and Supply Chain : 6th International Conference, ILS 2016, Bordeaux, France, June 1–4, 2016, Revised Selected Papers /: 6th International Conference, ILS 2016, Bordeaux, France, June 1–4, 2016, Revised Selected Papers. (2018) - Unknown
No abstract available